2023
DOI: 10.1057/s41599-023-01554-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of media on preventive behaviour during the COVID-19 pandemic

Abstract: The novel coronavirus 2019 (COVID-19) pandemic required implementation of a variety of measures. In addition to pharmaceutical measures, such as vaccines, changing individuals’ nonpharmaceutical preventive behaviour is essential to prevent the spread of infection. In uncertain situations, such as a pandemic, media sources are important for guiding individuals’ decision-making behaviour. In this study, we examined the effects of media use on preventive behaviour during COVID-19. Earlier studies have shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Previous research about the impact of news media on infectious diseases—including mpox, H1N1, Ebola, and COVID-19—has demonstrated that increased exposure to quality information through news and social media can increase vaccine uptake, 75,76 reduce disease transmission, 77 and encourage protective behaviors. 7880 Our work reflects the need for awareness campaigns during infectious disease crises, emphasizing proper nomenclature as well as providing high-quality information on disease spread and populations most at-risk. Future research evaluating media communications regarding the mpox name change may provide valuable insights into how the news media referred to the disease over time; whether there were any political, geographical, or temporal trends; and what messaging at what time point corresponded to higher uptake of ‘mpox’.…”
Section: Discussionmentioning
confidence: 90%
“…Previous research about the impact of news media on infectious diseases—including mpox, H1N1, Ebola, and COVID-19—has demonstrated that increased exposure to quality information through news and social media can increase vaccine uptake, 75,76 reduce disease transmission, 77 and encourage protective behaviors. 7880 Our work reflects the need for awareness campaigns during infectious disease crises, emphasizing proper nomenclature as well as providing high-quality information on disease spread and populations most at-risk. Future research evaluating media communications regarding the mpox name change may provide valuable insights into how the news media referred to the disease over time; whether there were any political, geographical, or temporal trends; and what messaging at what time point corresponded to higher uptake of ‘mpox’.…”
Section: Discussionmentioning
confidence: 90%
“…This study includes 32 studies conducted in 20 countries globally in which, six studies in USA [ 44 – 49 ], China five [ 34 , 50 – 53 ] Malaysia three,[ 54 – 56 ], Korea two[ 57 , 58 ] Pakistan [ 59 ], Spain [ 60 ], Poland and Jordan [ 61 ], Indonesia [ 62 ], Guatemala [ 63 ], Japan [ 64 ], Jordan [ 31 ], Vietnam [ 65 ], Bangladesh [ 66 ], Ethiopia [ 67 ], Italy [ 68 ], Nigeria [ 69 ], Saudi Arabia [ 70 ], Canada [ 71 ], SSA [ 72 ], and in United States, Mexico, the United Kingdom, Germany, and Spain, [ 73 ] one study in each country. Most of the studies were cross-sectional study design except five, which were experimental studies.…”
Section: Resultsmentioning
confidence: 99%
“…One particularly effective way to use social media platforms to promote dialogue is by raising public awareness and sensitization about the COVID-19 prevention campaign. Facebook campaigns, for example, have shared information and sparked discussions about pertinent COVID-19 emergency topics between scientists and the general public [ 57 , 58 , 64 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation